2019
DOI: 10.1002/chem.201903732
|View full text |Cite
|
Sign up to set email alerts
|

Computer Modelling and Synthesis of Deoxy and Monohydroxy Analogues of a Ribitylaminouracil Bacterial Metabolite that Potently Activates Human T Cells

Abstract: 5-(2-Oxopropylideneamino)-6-d-ribitylaminouracil (5-OP-RU) is an atural productf ormedd uring bacterial synthesis of vitamin B2. It potently activates mucosal associated invariant T( MAIT) cells and has immunomodulatory,i nflammatory,a nd anticancer properties. This highly polar and unstable compound forms ar emarkablys table Schiff base with al ysine residuei nm ajor histocompatibility complex class Irelated protein (MR1) expressed in antigen-presentingc ells. Inspiredb yt he importance of the ribityl moiety … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
19
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

3
5

Authors

Journals

citations
Cited by 16 publications
(20 citation statements)
references
References 41 publications
1
19
0
Order By: Relevance
“…Indeed, Awad et al. reported that subtle modifications of 5‐OP‐RU, including deoxy analogues, had a profound impact on their chemical stability [18] . Thus, prior to evaluating the T cell activation, we first investigated the chemical stability of four diastereomers [ 1 a and its stereoisomers 1 c , 1 e and 1 g ] prepared from the corresponding 5‐A‐RU stereoisomers.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Indeed, Awad et al. reported that subtle modifications of 5‐OP‐RU, including deoxy analogues, had a profound impact on their chemical stability [18] . Thus, prior to evaluating the T cell activation, we first investigated the chemical stability of four diastereomers [ 1 a and its stereoisomers 1 c , 1 e and 1 g ] prepared from the corresponding 5‐A‐RU stereoisomers.…”
Section: Resultsmentioning
confidence: 99%
“…The ribityl group of 5‐OP‐RU is mainly recognized by TCR on MAIT cells [14] . For investigating the molecular recognition by MR1 and MAIT‐TCR, and the chemical stability, several structure‐activity relationship (SAR) studies of 5‐OP‐RU have been carried out by various approaches [17–22] . For instance, Mak et al.…”
Section: Introductionmentioning
confidence: 99%
“…Despite chemical modifications to the natural antigen 5-OP-RU, the synthetic analog MAgA-TAMRA was still able to traffic to the ER, bind to MR1 molecules, and inhibit MAIT cell recognition of other ligands. MAgA-TAMRA helps to further define the structural limitations and ligand tolerance in the Ag binding cleft of MR1, which can accommodate a variety of small molecules (47), and it serves as a blueprint for creating new MR1 ligands customized with different payloads and functionalities for studying MR1 biology (5,48,49).…”
Section: Discussionmentioning
confidence: 99%
“…5‐Amino‐6‐(2‐deoxy‐D‐ribitylamino)uracil (5‐A‐(2‐deoxy)RU) 30,67 was prepared by reduction with 4.5 eq of sodium dithionite of the 5‐nitroso‐6‐(2‐deoxy‐D‐ribitylamino)uracil precursor, 67 as previously described for 5‐A‐RU 66 and was stored at −80℃ until required for biological studies. Analysis by liquid chromatography‐mass spectrometry (LC‐MS) indicated the formation of 5‐A‐(2‐deoxy)RU (Figure ).…”
Section: Methodsmentioning
confidence: 99%